Understanding perspectives on major system change: A comparative case study of public engagement and the implementation of urgent and emergency care system reconfiguration. Issue 7 (July 2017) - Foley, Conor; Droog, Elsa; Healy, Orla; McHugh, Sheena; Buckley, Claire; Browne, John Patrick
Highlights: Public engagement activities can influence public opinion of health service reconfiguration. Inadequate engagement can foster public opposition to changes, potentially hampering implementation. Interactive, genuine and ongoing engagement can address public concerns and facilitate implementation. Opposition to change is typically localised in character. Abstract: Objectives: Major changes have been made to how emergency care services are configured in several regions in the Republic of Ireland. This study investigated the hypothesis that engagement activities undertaken prior to these changes influenced stakeholder perspectives on the proposed changes and impacted on the success of implementation. Methods: A comparative case-study approach was used to explore the changes in three regions. These regions were chosen for the case study as the nature of the proposals to reconfigure care provision were broadly similar but implementation outcomes varied considerably. Documentary analysis of reconfiguration planning reports was used to identify planned public engagement activities. Semi-structured interviews with 74 purposively-sampled stakeholders explored their perspectives on reconfiguration, engagement activities and public responses to reconfiguration. Framework analysis was used, integrating inductive and deductive approaches. Results: Approaches to public engagement and success of implementation differed considerably across the three cases. Regions that presented the public with the reconfiguration plan alone reported greater public opposition and difficulty in implementing changes. Engagement activities that included a range of stakeholders and continued throughout the reconfiguration process appeared to largely address public concerns, contributing to smoother implementation. Conclusions: The presentation of reconfiguration reports alone is not enough to convince communities of the case for change. Genuine, ongoing and inclusive engagement offers the best opportunity to address community concerns about reconfiguration.